Decision Support Model to Select Cushioning Material for Dynamics Hazards During Transportation - Mojzes, Á.; Böröcz, P. (Acta Technica Jaurinensis, 2015)
Designing a product-packaging system is a complex challenge for engineers. Building a suitable and sustainable system the packaging engineers have to take into consideration many aspects, demands and requirements. To protect the product by packaging-system from physical events during transportation, handling and warehousing the cushioning has got a significant role, because this means the primary protection. This paper aims to give a model help to decide the applicability of different cushioning materials based on their protective, sustainable and economical attributions. This model ranks the different types of packaging materials choosing the final optimal solution. Our study also introduces a determinant, which is in connection with the mechanical characteristic (cushion curve) of the material on different environmental factors.